FINDING THE OPTIMAL POWER TRANSMISSION PARAMETERS POSITIONAL CODES IN AUTOMATED CONTROL SYSTEMS - S. G. Rassomahin; O. P. Malofey; A. O. Malofey (Наука. Инновации. Технологии)
Considered the method of improving the quality of positional numbers based on OFDM signals, which use additional amplitude shift keying quadrature components. Optimization problem is solved by the redistribution of energy between the carrier frequencies. The possibility of reducing the relative power of the noise 10-15 dB without additional energy expenditure.